2005
DOI: 10.1021/ja051694k
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of RNAs with up to 100 Nucleotides Containing Site-Specific 2‘-Methylseleno Labels for Use in X-ray Crystallography

Abstract: The derivatization of nucleic acids with selenium is a new and highly promising approach to facilitate their three-dimensional structure determination by X-ray crystallography. Here, we report a comprehensive study on the chemical and enzymatic syntheses of RNAs containing 2'-methylseleno (2'-Se-methyl) nucleoside labels. Our approach includes the first synthesis of an appropriate purine nucleoside phosphoramidite building block. Most importantly, a substantially changed RNA solid-phase synthesis cycle, compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…The 29-SeCH 3 -labeling method, suited for the determination of RNA structures, relies on the crystallization of RNA molecules that have natural nucleoside(s) substituted for their 29-SeCH 3 -modified counterparts during chemical RNA synthesis. The 29-SeCH 3 labeling allows use of the powerful multiwavelength anomalous dispersion (MAD) technique for structure determination and, in contrast to the halogenation of pyrimidines, can be utilized for the modification of all four standard nucleosides (adenosine, guanosine, uridine, and cytidine) (Hobartner and Micura 2004;Hobartner et al 2005;Moroder et al 2006;Puffer et al 2008). Moreover, the combination of the 29-SeCH 3 labeling with enzymatic ligation expands the z40 nucleotide (nt) limit of chemically synthesized Se-labeled RNA to large biologically relevant RNA molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The 29-SeCH 3 -labeling method, suited for the determination of RNA structures, relies on the crystallization of RNA molecules that have natural nucleoside(s) substituted for their 29-SeCH 3 -modified counterparts during chemical RNA synthesis. The 29-SeCH 3 labeling allows use of the powerful multiwavelength anomalous dispersion (MAD) technique for structure determination and, in contrast to the halogenation of pyrimidines, can be utilized for the modification of all four standard nucleosides (adenosine, guanosine, uridine, and cytidine) (Hobartner and Micura 2004;Hobartner et al 2005;Moroder et al 2006;Puffer et al 2008). Moreover, the combination of the 29-SeCH 3 labeling with enzymatic ligation expands the z40 nucleotide (nt) limit of chemically synthesized Se-labeled RNA to large biologically relevant RNA molecules .…”
Section: Introductionmentioning
confidence: 99%
“…A second approach described by Crothers and coworkers showed that sequence specific RNase H cleavage of an unlabeled and a labeled RNA can be followed by direct cross re-ligation of a labeled with an unlabeled fragment using T4 DNA ligase [145]. Finally, two groups presented another approach that combines the use of both T4 RNA and T4 DNA ligase in order to obtain multiple segmental isotopically labeled RNAs (i.e: three RNA fragments ligation) [139,146,147].…”
Section: Selective Isotope Labeling For Larger Rnasmentioning
confidence: 99%
“…In addition to these problems, RNA molecules are prone to misfolding and adopting alternative conformations [11][12][13][14][15]. Moreover, once crystals are obtained, phasing for RNA crystals remains time-consuming and challenging compared with selenium-assisted phasing of protein crystals [11,16,17]. These problems have led RNA researchers to develop creative approaches to circumvent or ameliorate some of the problems.…”
Section: The Problem Of Rna Crystallizationmentioning
confidence: 99%